2011
DOI: 10.1159/000330631
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Biological Properties of a Recombinant Dodecahedron Containing the Short Fiber Protein of the Human Adenovirus 41

Abstract: Objective: In order to gain further insight into the function of the enteric adenovirus short fiber (SF), we have constructed a recombinant dodecahedron containing the SF protein of HAdV-41 and the HAdV-3 penton base. Methods: Recombinant baculoviruses expressing the HAdV-41 SF protein and HAdV-3 penton base were cloned and amplified in Sf9 insect cells. Recombinant dodecahedra were expressed by coinfection of High Five™ cells with both baculoviruses, 72 h post-infection. Cell lysate was centrifuged on sucrose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Since the penton base/fiber interaction mechanism is conserved between several adenovirus serotypes [7], fiber-pseudotyped dodecahedrons are produced. This has been demonstrated by the in vitro addition of the long HAdV2 fiber on Bs-Dd [31] or by coexpression of the HAdV3 Bs-Dd with the 'short' fiber of the enteric serotype HAdV41 in insect cells [29]. This result elegantly showed that fibers from serotypes, for which the penton base cannot dodecamerize (HAdV2, HAdV41), can be artificially dodecamerized on the HAdV3-derived Bs-Dd scaffold (Figure 3).…”
Section: Recombinant Dodecahedronsmentioning
confidence: 82%
See 1 more Smart Citation
“…Since the penton base/fiber interaction mechanism is conserved between several adenovirus serotypes [7], fiber-pseudotyped dodecahedrons are produced. This has been demonstrated by the in vitro addition of the long HAdV2 fiber on Bs-Dd [31] or by coexpression of the HAdV3 Bs-Dd with the 'short' fiber of the enteric serotype HAdV41 in insect cells [29]. This result elegantly showed that fibers from serotypes, for which the penton base cannot dodecamerize (HAdV2, HAdV41), can be artificially dodecamerized on the HAdV3-derived Bs-Dd scaffold (Figure 3).…”
Section: Recombinant Dodecahedronsmentioning
confidence: 82%
“…This has been shown to be the case during the replication cycle of serotypes 4, 7, 9, 11, and 15 [22][23][24][25]. In contrast, there is no evidence that serotypes 1, 2, 5, 6, 12, 16, 40, and 41 can produce such dodecahedrons [26][27][28][29]. It is also worth noticing that none of the well-studied subgroup C serotypes are able to produce dodecahedrons and that, in subgroup B, dodecahedron production is serotype-dependent (Table 2).…”
Section: Discovery and Spontaneous Productionmentioning
confidence: 96%